2022
DOI: 10.1002/ange.202210804
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Reactive Oxygen Species Generation Using Inter‐Facet Edge Rich WO3 Arrays for Photoelectrochemical Conversion

Abstract: Water oxidation reaction leaves room to be improved in the development of various solar fuel productions, because of the kinetically sluggish 4‐electron transfer process of oxygen evolution reaction. In this work, we realize reactive oxygen species (ROS), H2O2 and OH⋅, formations by water oxidation with total Faraday efficiencies of more than 90 % by using inter‐facet edge (IFE) rich WO3 arrays in an electrolyte containing CO32−. Our results demonstrate that the IFE favors the adsorption of CO32− while reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Recently, the reactive oxidizing species such as H 2 O 2 , OH·, etc. were demonstrated to be involved as key intermediates for PEC water oxidation on WO 3 photoanodes under acid conditions, which were utilized for the PEC oxidation of benzyl alcohol, methane, etc. , To provide insight into the current stability in the bulk photoelectrolysis for PEC water oxidation (Figure ), the catalytic performances for PEC oxidation of benzyl alcohol to benzaldehyde was investigated over NW- and HP-WO 3 electrodes. LSVs of NW- and HP-WO 3 electrodes in the presence and absence of benzyl alcohol (0.1 mmol) in a 0.5 M Na 2 CO 3 solution (pH 3.0) with chopped visible light irradiation are shown in Figure A,B, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the reactive oxidizing species such as H 2 O 2 , OH·, etc. were demonstrated to be involved as key intermediates for PEC water oxidation on WO 3 photoanodes under acid conditions, which were utilized for the PEC oxidation of benzyl alcohol, methane, etc. , To provide insight into the current stability in the bulk photoelectrolysis for PEC water oxidation (Figure ), the catalytic performances for PEC oxidation of benzyl alcohol to benzaldehyde was investigated over NW- and HP-WO 3 electrodes. LSVs of NW- and HP-WO 3 electrodes in the presence and absence of benzyl alcohol (0.1 mmol) in a 0.5 M Na 2 CO 3 solution (pH 3.0) with chopped visible light irradiation are shown in Figure A,B, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The gas phases (headspaces) of both the working and counter electrode compartments were analyzed for the evolved O 2 and H 2 , respectively, using gas chromatography (Shimadzu, GC-8A with a TCD detector and molecular sieve 5 Å column and Ar carrier gas). PEC oxidation of benzyl alcohol was performed in a two-compartment cell separated by a Nafion membrane, referring to the literature . NW- or HP-WO 3 working and Ag/AgCl reference electrodes were placed in one compartment, and a Pt wire counter electrode was placed in the other compartment.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Sayama et al based on WO 3 /BiVO 4 heterojunction structure, deposited a series of overlayer (SiO 2 , ZrO 2 , TiO 2 , Al 2 O 3 , CoO x ) (Figure 11c). 32 Compared to a bare WO 3 /BiVO 4 photoanode, the 2e 98 WO 3 is an oxide with a deep VB position and has the potential for the production of H 2 O 2 via 2e − WOR. Its boundary has active components different from the intrinsic structure, which can effectively regulate the product selectivity in PEC WOR electrocatalysis.…”
Section: Strategies To Enhance H 2 O 2 Production Efficiency Through Pecmentioning
confidence: 99%
“…Inspired by the facet engineering effect of ZnO, Zhang’s group demonstrated that interfacet edge (IFE) rich WO 3 arrays have the ability to kinetically accelerate sluggish H 2 O 2 production of 2e – WOR . WO 3 is an oxide with a deep VB position and has the potential for the production of H 2 O 2 via 2e – WOR.…”
Section: Strategies To Enhance H2o2 Production Efficiency Through Pecmentioning
confidence: 99%